1997
DOI: 10.1091/mbc.8.11.2157
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a G2-Phase Arrest inXenopusEgg Extracts by Activation of p42 Mitogen-activated Protein Kinase

Abstract: Previous work has established that activation of Mos, Mek, and p42 mitogen-activated protein (MAP) kinase can trigger release from G2-phase arrest in Xenopus oocytes and oocyte extracts and can cause Xenopus embryos and extracts to arrest in mitosis. Herein we have found that activation of the MAP kinase cascade can also bring about an interphase arrest in cycling extracts. Activation of the cascade early in the cycle was found to bring about the interphase arrest, which was characterized by an intact nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 63 publications
(85 reference statements)
7
46
2
Order By: Relevance
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here. However, two highly cited reports concluded that wee1 is degraded in the early embryonic cell cycles (Michael and Newport, 1998;Ayad et al, 2003).…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 71%
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here. However, two highly cited reports concluded that wee1 is degraded in the early embryonic cell cycles (Michael and Newport, 1998;Ayad et al, 2003).…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 71%
“…First, addition of Aur-A protein during interphase does not lead to a detectable increase in Mos (H. Wu and J.V.R., unpublished data). Second, addition of Mos or MAP kinase blocks mitotic entry rather than accelerating it (36,37). CPEB-dependent translation of cyclin B1 is required for mitotic entry in egg extracts (38) and overexpression of Aur-A enhances polyadenylation of cyclin mRNA in somatic cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…In mitotic Xenopus egg extracts, MEK is active and required for normal mitotic progression (Abrieu et al, 1997;Walter et al, 1997;Bitangcol et al, 1998;Murakami and Vande Woude, 1998). MEK inhibition causes defects in both spindle formation (Horne and Guadagno, 2003) and spindle checkpoint control (Minshull et al, 1994;Takenaka et al, 1997;Chung and Chen, 2003).…”
Section: Introductionmentioning
confidence: 99%